A seismic upgrading method for steel arch bridges using buckling-restrained braces. - Usami, Tsutomu (Earthquake engineering & structural dynamics.)
In this study the employment of buckling-restrained braces (BRBs) as energy dissipation dampers is attempted for seismic performance upgrading of steel arch bridges and the effectiveness of BRBs to protect structures against strong earthquakes is numerically studied. With buckling restrained, BRB members can provide stable energy dissipation capacity and thus damage of the whole structure under major earthquakes can be mitigated. Cyclic behaviour of such members is addressed with a numerical simulation model, and a strength design method for BRBs is proposed. BRBs are then placed at certain locations on the example steel arch bridge to replace some normal members with two schemes, and the effect of the two installation schemes of BRBs for seismic upgrading is investigated by non-linear time-history analyses under various ground motions representing major earthquake events. Compared with the seismic behaviour of the original structure without BRBs, satisfactory seismic performance is seen in the upgraded models, which clarifies the effectiveness of the proposed upgrading method and it can serve as an efficient solution for earthquake resistant new designs and retrofit of existing steel arch bridges.